2021
DOI: 10.1002/aoc.6255
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable approach for efficient one‐pot synthesis of 1‐aryl 1,2,3‐triazoles using copper iodide supported on 3‐thionicotinyl‐urea‐modified magnetic nanoparticles in DES

Abstract: An efficient and retrievable copper(I) catalyst was synthesized by immobilizing of copper iodide on 3‐thionicotinyl‐urea‐modified magnetic nanoparticles and characterized using a variety of analysis techniques. The catalytic activity of these nanoparticles was investigated in the one‐pot three‐component reaction of aryl halides, sodium azide, and terminal alkynes using choline chloride/PEG deep eutectic mixture as a green and recoverable solvent. The PEGylated deep eutectic solvent (DES), due to its favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In the complex (Figure 2B), in addition to the two stages of decomposition corresponding to the breaking of bromo methyl propanoate and Pyridyl/Triazole moieties (first & second stages of decomposition), one more decomposition occurred above between 526.6 to 599.1 °C with the weight loss of 21.34 %. The steep decomposition which occurs after 500 °C is possibly due to the breaking of copper iodide with the sublimation of iodine [43–45] . More importantly, upon comparing the TGA of the free ligand and its complex, it was observed that upon binding with Cu (I), both the first and second stages of decomposition occurred at slightly higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the complex (Figure 2B), in addition to the two stages of decomposition corresponding to the breaking of bromo methyl propanoate and Pyridyl/Triazole moieties (first & second stages of decomposition), one more decomposition occurred above between 526.6 to 599.1 °C with the weight loss of 21.34 %. The steep decomposition which occurs after 500 °C is possibly due to the breaking of copper iodide with the sublimation of iodine [43–45] . More importantly, upon comparing the TGA of the free ligand and its complex, it was observed that upon binding with Cu (I), both the first and second stages of decomposition occurred at slightly higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42] During the second stage of decomposition, °C is possibly due to the breaking of copper iodide with the sublimation of iodine. [43][44][45] More importantly, upon comparing the TGA of the free ligand and its complex, it was observed that upon binding with Cu (I), both the first and second stages of decomposition occurred at slightly higher temperatures. Thus, the first and the second stages of decomposition occurred between 235.7 to 323.1 and 323.1 to 452.3 °C, respectively, indicating the ligand's stabilization upon coordination with metal ions.…”
Section: Synthesis and Characterization Of Copper (I) Complexes (Comp...mentioning
confidence: 99%
“…85 In another study, Mirshafiee et al focused on a sustainable strategy for one-pot synthesis of 1-aryl 1,2,3-triazoles using ChCl/PEG deep eutectic mixture as green solvent, forming an influential association between polar and non-polar reactants during the reaction. This approach accelerated the catalysis process using retrievable copper(I) catalyst immobilized 3-thionicotinyl-urea-modified magnetic NPs, resulting in moderate to excellent yields, 86 as in Table 2, entry (18). In the pursuit of synthesizing a series of 1,4-disubstituted 1,2,3-triazole-thiazolidinone-carvone hybrids, Itto and the group demonstrated a CuAAC reaction.…”
Section: Solvents Other Than Watermentioning
confidence: 99%
“…Thus, the mixtures ascorbic acid:choline chloride (1:2) and glycolic acid:trimethylglycine (2:1) were effectively used as solvents and avoided the need of using external bases or reducing agents, with the solvent being recyclable up to three times without loss of activity ( Table 2 , entry 4) [ 30 ]. In addition, a heterogeneous catalyst based on copper iodide supported on 3-thionicotinyl-urea-modified magnetic nanoparticles was also employed to perform this transformation using ChCl:PEG (1:4) as a solvent ( Figure 11 ) [ 31 ].…”
Section: Cyclization Reactionsmentioning
confidence: 99%